Allelopathic effect of selected rice (Oryza sativa) varieties against Barnyard Grass (Echinochloa cruss-gulli) - Rahaman, Ferdoushi; Juraimi, Abdul Shukor; Yusop, Mohd Rafii; Uddin, Md. Kamal; Hassan, Lutful; Chowdhury, Abul Kashem; M. Khairul, Bashar H. (Multidisciplinary Digital Publishing Institute, 2021)
Rice has been subjected to a great deal of stress during its brief existence, but it nevertheless ranked first among cereal crops in terms of demand and productivity. Weeds are characterized as one of the major biotic stresses by many researchers. This research aims to determine the most potential allelopathic rice variety among selected rice accessions. For obtaining preeminent varieties, seventeen rice genotypes were collected from Bangladesh and Malaysia. Two prevalent procedures, relay seeding and the sandwich technique were employed to screen the seventeen rice (donor) accessions against barnyard grass (tested plant). In both approaches, only the BR17 variety demonstrated substantial inhibition of germination percentage, root length, and dry matter of barnyard grass. The rice variety BR17 exclusively took the zenith position, and it inhibited the development of barnyard grass by more than 40–41% on an average. BR17 is originated from KN-1B-361-1-8-6-10 (Indonesia) and developed by the Bangladesh Rice Research Institute (BRRI), Gazipur, Bangladesh in 1985, having a high yielding capacity of more than 6 t/ha. Our study suggested that the usage of the allelopathy-weed inverse relationship to treat the weed problem can be a fantastic choice in the twenty-first century.